Management of Anesthesia in Patient with Osteogenesis Imperfecta Type IV and Fractures on Tibia and Fibula: A Case Report - Kenzi, Ignatio Armando; Otniel Adrians Labobar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Osteogenesis imperfecta (OI), known as brittle bone disease, is a rare inherited and genetic skeletal disorder characterized by a significantly heightened risk of fragility fractures. About 1 in 15 to 20.000 births are affected with OI. these defects may moreover be combined with an airway that's troublesome to oversee, platelet dysfunctions, and other issues. The perioperative administration of anesthesia speaks to a significant challenge. Subsequently, it is critical to be able to anticipate the dangers during the perioperative period and to define and actualize particular high-quality anesthesia administration plans for such patients when they involve injury. Case presentation: We present a case of a female patient 26 years old with known OI type IV who underwent Osteotomy and Open Reduction Internal Fixation with plate and screw (ORIF PS) on her left Tibia and Fibula. In this case, we present the anesthesia technique with general anesthesia using a metal wire-enforced endotracheal tube to prevent partial obstruction due to kyphoscoliosis. Conclusion: It is crucial to assess the severity of the disease, identify risk factors in advance, and optimize the preoperative health status of individuals with OI.